عبد الرحمان حسن حبنكة الميداني وجهوده في خدمة العقيد ة من خلال كتابه العقيد الاسلامية وأسسها - راضية, رقيق; حنان, هيبة (جامعة الوادي university of eloued, 2017)
الملخص باللغتين العربية واإلنجليزية ملخص البحث : احلمدهللربالعاملنيوالصالةوالسالمعلىأشرفاملرسلنينبيناحممدوعلىآلهوصحبهأمجعني .أمابعد: جاءهذاالبحثمشتمالعلىمقدمةومخسةمباحثوخامتة. اشتملتاملقدمةعلىمتهيد,واإلشكاليةاملراداإلجابةعليهايفثناياالبحث,أمهيةاملوضوع وأهدافه,وأسباباختيارناله,والدراساتالسابقة,واملراجعواملصادر,واملنهجاملتبعيفالبحث,وأهم اخلطواتاليتسرناعليهاوحدودهذهالدراسةوالصعوباتاليتواجهتنايفحبثناوخطةالبحث موجزة. ــــتعرفنايفاملبحثاألولعلىأهممصطلحاتعنوانالبحثمنخاللكتباللغةاملعتمدةيف مفهومهااللغويأماالناحيةاالصطالحيةفقدرجعناإيلكتبالعقيدةوالتفسري. تكلمنايفاملبحثالثاينعنترمجةالشيخعبدالرمحانامليداينمنخاللمارجعناإليهمنمراجع. ـــتعرفناعلىكتابالعقيدةاإلسالميةوأسسهايفاملبحثالثالثوذكرناسببودوافعامليداين لتأليفهالكتابوعرفناموضوعالكتاباألساسيومنهجالشيخفيه. ـــويفاملبحثالرابعتعرضاملنهجعبدالرمحانامليداينيفعرضاإلميانيفأسسالعقيدةالست. ــــأمااملبحثاخلامساألخريفقدتطرقناإىلدفاعالشيخعنعقيدةأهلالسنةواجلماعةيفبعض املسائلالعقديةكالردعلىمنكريالبعثوإبطالبدعةاجملسمةواملشبهة,وبيانخمالفةاجلربية واملعتزلةلعقيدةالسلف,وردهعلىامللحدين,وبيانعقائدبعضالفرقالضالة. ـــوأمااخلامتةفذكرنافيهاأهمالنتائجاليتتوصلناإليهايفهذاالبحثومنها: 1.يعتربالشيخعبدالرمحانامليداينموسوعةعلميةيفجماالتكثريةكالعقيدةوالتفسريوالبالغة وأنهمنأبرزأعالمعصره. 2.معرفةقيمةكتابالعقيدةاإلسالميةوأسسهاوموضوعهالعاموأنهاشتملعلىمعظم موضوعاتالعقيدةوأنهأولمؤلفاتالشيخامليداين. 3.خدمةالشيخعبدالرمحانامليداينللعقيدةاإلسالميةمنخاللكتابهالعقيدةاإلسالمية وأسسهاوجهودهاجلليةيفالكتابيفدفاعهعنالعقيدةالصحيحةوإثباهتا. الملخص باللغتين العربية واإلنجليزيةAbstract in Arab English Research Summary : Praise be to Allah ,lord of the worlds and may the blessings and peace of Allah be upon the most honored of messengers our master Mohammed and upon all his family and companions . This research includes an introduction , five sections and a conclusion. The introductusion contains a preface and problematic and the answers of them in this research ,the importance of the topic and Its aim , the causes of our choice of it and the previous studies ,references and resources , the followed ,method in the research , the important steps that we follow and the study limits and difficulties that we face in this research the summary research strategy. We know in section one about the important terms and title of the research through literature books based on lingual concept . bat about the term side we refer to belief and imterpretatios books. In section two we speat about a biography about sheikh abdelrahman el.midani thuough different referenos. We know the belicf books and its basics in section three and we mention the motives and reasons of sheikh midani for writing this book and we know thebacik tobic of the book and the strategy of sheik in it. In section four, we mention the strategy of sheikh in expoing the belief in the six belief bosics. In section five and the last one ,we speak about how sheikh defends the followers of algebraic and alienated to the doctrine of the predecessor and how to reply agaimst the atheists and charification of some stray teams doctrines . In conclusion ,we mention the imbortant ressilts that rue reach in this research which are: 1- Sheikh Abderhahmen midani is considred as a scientific encyclobedia in different fields as doctrine ,interpretation and rhetoric ,he is also the most prominent scientists in his era. 2-knowledge of the value of the Islamic creed book ,its basics and its general topic which contains most of the doctrine topics and the first midani's works . 3-The work of sheikh Abderahman midani for the Islamic doctrine through his book the Islamic doctrine and its basics and his good defending about the true doctrine and its pro
مقارنة